2006
DOI: 10.1523/jneurosci.4020-06.2006
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Activation of Inwardly Rectifying Potassium Channels by Immobile G-Protein-Coupled Receptors

Abstract: G-protein-coupled receptors (GPCRs) mediate slow synaptic transmission and many other effects of small molecule and peptide neurotransmitters. In the standard model of GPCR signaling, receptors and G-proteins diffuse laterally within the plane of the plasma membrane and encounter each other by random collision. This model predicts that signaling will be most efficient if both GPCRs and G-proteins are free to diffuse, thus maximizing collision frequency. However, neuronal GPCRs are often recruited to and enrich… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 38 publications
0
22
0
Order By: Relevance
“…We have previously shown that similar fluorescent protein-mOR fusion proteins are functional when immobilized on the cell surface (Lober et al, 2006). Accordingly, agonist stimulation (10 mM DAMGO) rapidly redistributed V-arrestin3 from the cytosol to the bead-associated plasma membrane in cells expressing His-C-mOR (Supplemental Fig.…”
Section: Resultsmentioning
confidence: 93%
“…We have previously shown that similar fluorescent protein-mOR fusion proteins are functional when immobilized on the cell surface (Lober et al, 2006). Accordingly, agonist stimulation (10 mM DAMGO) rapidly redistributed V-arrestin3 from the cytosol to the bead-associated plasma membrane in cells expressing His-C-mOR (Supplemental Fig.…”
Section: Resultsmentioning
confidence: 93%
“…Yet, despite this highly transient nature, the FRAP of ␤ 1 ␥ 2 -activated PLC␤ 2 (or PLC␤ 2 ⌬) is strongly dominated by fast lateral diffusion (Figs. 4 and 5), characterized by D values 3-to 5-fold faster than lipids or lipidanchored proteins such as G protein ␣ or ␤␥ subunits (7,32,34,62,63). Combining the highly transient interactions and the very fast diffusion along the plasma membrane, we propose that stimulation by ␤ 1 ␥ 2 induces surfing-like diffusion of PLC␤ 2 enzymes along the cytoplasmic face of the plasma membrane.…”
Section: Discussionmentioning
confidence: 91%
“…Nevertheless, the association of ␣ q -stimulated PLC␤ 2 with membrane constituents (including ␣ q itself) must be dynamic, as indicated by the contribution of exchange to the FRAP kinetics (Fig. 4) and by the lower D value (0.47 m 2 /s) measured for a G␣ subunit (␣ oA ) (63). Based on the D and ex values, the travel range of ␣ q -stimulated PLC␤ 2 is estimated to be 0.75 m, suggesting that PLC␤ 2 recruited by ␣ q stimulation is less constrained than the Rac2-stimulated enzyme, roaming larger (albeit still limited) membrane regions.…”
Section: Discussionmentioning
confidence: 99%
“…Where functional studies have been done using the activation of GIRK-dependent currents, precoupling has been suggested (Zhang et al, 2002;Lober et al, 2006;Zhou et al, 2012). Those experiments examined receptors (including MOR) that were immobilized, and the mobility of G proteins, GIRK channels, or RGS proteins was assayed (Zhang et al, 2002;Lober et al, 2006;Zhou et al, 2012).…”
Section: Functional Mors After Desensitization Discussionmentioning
confidence: 99%